Inhibitory effects of apigenin on the growth of gastric carcinoma SGC-7901 cells - Wu, Kun (World J Gastroenterol, 2005)
AIM: To explore the growth inhibition and apoptosis-inducing effect of apigenin on human gastric carcinoma SGC-7901 cells. METHODS: The effects of apigenin on the growth, clone formation and proliferation of human gastric carcinoma SGC-7901 cells were observed by MTT, clone-forming assay, and morphological observation. Fluorescent staining and flow cytometry analysis were used to detect apoptosis of cells. RESULTS: Apigenin obviously inhibited the growth, clone formation and proliferation of SGC-7901 cells in a dose-dependent manner. Inhibition of growth was observed on d 1 at the concentration of 80 μmol/L, while after 4 d, the inhibition rate (IR) was 90%. The growth IRs at the concentration of 20, 40, and 80 μmol/L were 38%, 71%, and 99% respectively on the 7(th) d. After the cells were treated with apigenin for 48 h, the number of clone-forming in control, 20, 40, and 80 μmol/L groups was 217±16.9, 170±11.1 (P<0.05), 98±11.1 (P<0.05), and 25±3.5 (P<0.05) respectively. Typical morphological changes of apoptosis was found by fluorescent staining. The cell nuclei had lost its smooth boundaries, chromatin was condensed, and cell nuclei were broken. Flow cytometry detected typical apoptosis peak. After the cells were treated with apigenin for 48 h, the apoptosis rates were 5.76%, 19.17%, and 29.30% respectively in 20, 40, and 80 μmol/L groups. CONCLUSION: Apigenin shows obvious inhibition on the growth and clone formation of SGC-7901 cells by inducing apoptosis.